Functions and Biotechnology of Plant Secondary Metabolites 2010
DOI: 10.1002/9781444318876.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modes of Action of Defensive Secondary Metabolites

Abstract: Secondary metabolites (SM) have been shaped by evolution for more than 500 million years. As a result, many of them have distinctive biochemical and pharmacological properties. The molecular modes of action of the main groups of SM are reviewed in this chapter. Details are given on interactions of SM with proteins that can induce conformational changes and thus a modification of their bioactivity. The fluidity and permeability of biomembranes constitute another important target, which is influenced by many lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 325 publications
(251 reference statements)
2
89
0
1
Order By: Relevance
“…To support this idea Eisenreich et al [ 209 ] showed that IPP involved in the biosynthesis of the taxane ring was formed via the MEP pathway. However, other studies [ 28 ] demonstrated the involvement of the cytosolic pathway. A recent study of T. baccata cell cultures showed that while taxol biosynthesis was blocked by the addition of fosmidomycin, an inhibitor of the plastid pathway, it was also reduced by mevinolin, an inhibitor of the cytosolic pathway, indicating that both pathways could be involved [ 210 ].…”
Section: Cell Cultures Both Callus and Suspension Have Been Obtainementioning
confidence: 95%
See 1 more Smart Citation
“…To support this idea Eisenreich et al [ 209 ] showed that IPP involved in the biosynthesis of the taxane ring was formed via the MEP pathway. However, other studies [ 28 ] demonstrated the involvement of the cytosolic pathway. A recent study of T. baccata cell cultures showed that while taxol biosynthesis was blocked by the addition of fosmidomycin, an inhibitor of the plastid pathway, it was also reduced by mevinolin, an inhibitor of the cytosolic pathway, indicating that both pathways could be involved [ 210 ].…”
Section: Cell Cultures Both Callus and Suspension Have Been Obtainementioning
confidence: 95%
“…In vivo biosynthesis of secondary metabolites is regulated by the plant signalling system and is not crucial for the survival of the individual cells [ 28 ]. In contrast, the auto-selection process in the dedifferentiated cell culture results in preferable production of metabolites that promote intensive and stable proliferation.…”
Section: )mentioning
confidence: 99%
“…We had shown before that harmine arrested MCF-7 cell growth and induced senescence ( Cytotoxicity can result from an adverse interaction of harmine and other alkaloids with one or more important targets present in a cell including DNA, RNA, or associated enzymes (Roberts & Wink, 1998;Wink & van Wyk, 2008;Wink, 2007). Harmine is known to intercalate DNA and through this it can cause mutations and DNA damage (Wink et al, 1998a;Wink & Schimmer, 2010). Through these interactions cell proliferation can be interrupted or cell death induced (Lansiaux et al, 2002;Möller et al, 2007;Wink, 2007).…”
Section: Reviewing Manuscriptmentioning
confidence: 99%
“…Included in this category are such well-known anti-defenses as alkaloids, amines, cyanogenic glycosides, non-protein amino acids, glucosinolates, alkamides and peptides (Wink & Schimmer, 2010). Most nitrogenous secondary metabolites are biosynthesized from common amino acids.…”
Section: Nitrogenous Compoundsmentioning
confidence: 99%
“…It´s has studied the secondary metabolites present in various plant species, one to identify its presence, chemical structure and effect on the plant and on other organisms, so that the number of Identified Substances exceed to 100 000 at present (Wink and Schimmer, 2010) Table 2. Distribution of polyphenols compounds on different phylum's in comparative to Plant phylum (Garcia, 2004, as cited in Harborne, 1990 The number of plant species containing one or more of the major groups of compounds with anti-fungal activity is very diverse (Glasby, 1991), in Isolimonene, Isopulegol, Carvone Naigre et al, 1996 5,7-Dihydroxy-4-hydroxyisoflavan, 6,7-Dihydroxy-4_-methoxyisoflavan, 5,7-Dihydroxy-4_- Table 3.…”
Section: Plants With Antifungal Propertiesmentioning
confidence: 99%